Recent Bank Support for Civil Service Reconstruction in Post-conflict Countries - World Bank (Washington, DC, 2012)
Civil service reconstruction is important in post-conflict countries because conflict erodes institutions and civil service capacity. And because successful reconstruction-in all sectors-requires domestic capacity to implement projects, a weak civil service undermines overall reconstruction efforts. Moreover, donor assistance is crucial to a country's rebuilding, and coordinating such assistance requires a certain amount of civil service capacity.